From SARS-CoV-2 to Influenza: Modern Pedagogical Approaches for Teaching Virology in Undergraduate Classrooms - Md Nazmul Hossen (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: The COVID-19 pandemic and influenza highlight the global necessity to enhance virology education within biomedical curricula. Conventional lectures often fail to facilitate critical thinking. This review aims to synthesize contemporary pedagogical approaches such as active learning and virtual laboratories to improve scientific reasoning. Methodology: A comprehensive literature search was conducted in PubMed, ERIC, Scopus, and Web of Science databases for the period 2015–2025. Keywords used included virology education and active learning. Out of 425 articles screened, 127 peer-reviewed papers met the eligibility criteria. Data were extracted regarding instructional design and student outcomes. Main Findings: Active learning increases STEM performance by 30% compared to passive lecturing. Case-based learning (CBL) improves critical thinking by 27% and enhances long-term retention. Virtual laboratories produce learning outcomes equivalent to traditional labs while reducing costs. Gamification and collaborative projects significantly boost student motivation, engagement, and self-efficacy. Novelty/Originality of this study: This review provides a new framework for integrating real-time pandemic data into undergraduate curricula. It uniquely addresses the gap between molecular virology and global health responses in resource-limited settings. By synthesizing recent digital advancements, it offers a roadmap for creating a scientifically literate workforce capable of managing future viral outbreaks.